Nurse-led insulin protocol efficacy for control of hyperglycemia in critically Ill patients - Nafisa Moustafa Abdallah Elpasiony; Ahmed Ali Hafez; Abdelaziz Hendy; Rasha Kadri Ibrahim; Mohamed Hashem Kotp; Nadiah A Baghdadi; Shimaa Ramadan Ahmed (BMC Nursing)
Abstract Background Hyperglycemia is frequently observed in critically ill patients and is linked to increased complications, prolonged ICU stays, and higher mortality. Traditional physician-led insulin management may lack the responsiveness required for optimal glycemic control. In contrast, nurse-led insulin infusion protocols offer a more timely and effective approach in the ICU setting. Aim This study evaluated the effectiveness of a nurse-led insulin infusion protocol in managing hyperglycemia among critically ill patients compared to conventional physician-directed care. Methods A quasi-experimental design was implemented in the ICU of Fayoum University Hospital, Egypt, from January to June 2024. A total of 80 adult patients with hyperglycemia were randomly assigned to either a nurse-led insulin infusion protocol group (n = 40) or a standard care group (n = 40). Key outcomes included time to achieve target blood glucose (BG) levels (110–149 mg/dl), frequency of BG monitoring, and ICU length of stay. Data were analyzed using SPSS software. Results Patients in the intervention group achieved significantly better glycemic control at all five time points (p < 0.001), with 62.5% reaching target BG levels within 1–2 days compared to 12.5% in the control group. Additionally, 52.5% of intervention patients had ICU stays of 3–4 days, whereas the same proportion in the control group stayed for more than 7 days (p < 0.001). The frequency of BG monitoring was also higher in the intervention group. Conclusion The nurse-led insulin infusion protocol significantly enhanced glycemic control and reduced ICU stay duration. These findings support integrating nurse-led protocols in ICU settings to improve patient outcomes, ensure timely interventions, and optimize resource utilization. Trial registration Pan African Clinical Trials Registry (PACTR), no: PACTR202506863203683, date of approval 04/06/2025.